2015
DOI: 10.1186/s40425-015-0090-0
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of circulating Her-2-reactive T-cells producing pro- and/or anti-inflammatory cytokines in elderly breast cancer patients

Abstract: BackgroundTreating elderly breast cancer patients remains a challenge but the increasing availability of immunotherapeutic approaches instills optimism that these tumours may also be susceptible to immune control. Because aging leads to a number of alterations in the immune system (“immunosenescence”) reflecting potential exhaustion which could compromise immunomodulatory antibody therapy, here we have assessed the immunocompetence of elderly breast cancer patients compared with a group of younger patients, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…This was shown to be the case in breast cancer (and so not limited to one potentially unusual tumour type) and also in older patients (and so not negatively affected by immune ageing). These results document that such combined ‘immune signatures’ do not necessarily apply solely to one type of cancer that might not have been representative, and also that the immune system of older patients (> 80 years of age) was functionally intact, at least in this respect . This is important, given the common perception that ageing of the immune system (‘immunosenescence’) contributes not only to decreased protection against infectious disease, but also cancer, as cited in many reviews (e.g.…”
Section: Assessment Of the Patient's Peripheral Immune Statusmentioning
confidence: 63%
“…This was shown to be the case in breast cancer (and so not limited to one potentially unusual tumour type) and also in older patients (and so not negatively affected by immune ageing). These results document that such combined ‘immune signatures’ do not necessarily apply solely to one type of cancer that might not have been representative, and also that the immune system of older patients (> 80 years of age) was functionally intact, at least in this respect . This is important, given the common perception that ageing of the immune system (‘immunosenescence’) contributes not only to decreased protection against infectious disease, but also cancer, as cited in many reviews (e.g.…”
Section: Assessment Of the Patient's Peripheral Immune Statusmentioning
confidence: 63%
“…HER-2 overexpression has become an important marker of poor prognosis in breast cancer patients [916]. Our group previously found that the Fu-Zheng-Xiao-Liu granules could inhibit the proliferation of drug-resistant MCF-7 cells and enhance the sensitivity of drug-resistant MCF-7 cells to a combination of chemotherapy drugs.…”
Section: Discussionmentioning
confidence: 99%
“…In support, it has been demonstrated that IL-15 enhances the activity of tumour-specific T cells via delaying or reversing senescence, as shown by lower expression of p 16 INK4a among other markers of senescence [ 179 ]. Indeed, recent research has indicated that the capacity of peripheral blood T cells to recognise and respond to tumour-associated antigens is a predictor of survival in several malignancies, including breast cancer [ 180 , 181 ], colon cancer [ 182 ], melanoma [ 183 , 184 ], and hepatocellular carcinoma [ 185 ].…”
Section: Do Immunosenescent Profiles Increase the Risk Of Cancer Amentioning
confidence: 99%